Establishing good dietary habits – capturing the minds of children - Joachim Westenhöfer (Public Health Nutrition, 2001)
Objective: To review the psycho-social research with respect to relevance for the development of nutritional education strategies. Results: The eating behaviour of the newborn baby is controlled by innate preferences and dislikes, and by biological self-regulation. These innate control-systems are modified by learning processes, most importantly by the mere exposure to unknown food, by social influences, and by associating the physiological consequences of food intake with taste cues. The last decades have witnessed a change of the social meaning of food and eating, and the social context of eating is subject to dramatic changes. While on the one hand, prevalence of overweight and obesity is increasing, even young children deliberately practise weight control measures ranging from selective food choice to self-induced vomiting thus including behaviours which are clearly symptomatic of eating disorders. Such behaviour is motivated by unrealistic conceptions of a healthy body weight and shape. Children are interested in a range of nutrition topics. However, these topics have to be related to direct perceivable benefits from nutrition. Conclusions: Educational strategies should: firstly, focus on providing a variety of foods, including a range of nutrient-dense ‘healthy’ food and encouraging children to taste it; secondly, provide a stable and predictive pattern of social eating occasions to promote the social meaning and importance of eating and to enable social learning of food preferences; and finally, encourage a positive body image by providing advice and reassurance regarding the range of healthy and acceptable body weights and shapes.